Past and Present Copyright Tribunals for Setting Royalties in the United States - Ruwe, Steve (The Columbia Journal of Law & the Arts, 2025)
I was asked to participate in The Kernochan Center’s Symposium addressing “Past, Present and Future of Copyright Licensing.” I noted that in light of my current role on the United States Copyright Royalty Board, my presentation and discussion participation would focus on the past and the present of statutory Copyright Licensing in the United States. I chose to exclude any personal outlook on the future of Copyright Licensing, leaving that to other participants. The same holds true for this Article, which adheres to the topics addressed in my presentation. Thus, as the Symposium and the public look to potential licensing solutions that may emerge amidst the development of Artificial Intelligence products, my hope is to offer a brief, and high-level, background on how the United States has approached statutory licensing in the copyright realm. In doing so, I often look to the Register of Copyright’s 2015/2016 study, Copyright and the Music Marketplace, and recommend that study as a far more comprehensive portrait of the music licensing landscape at it existed at the time—prior to the enactment of the Music Modernization Act in 2018. Additional Copyright Office publications are available with more comprehensive information regarding the statutory licenses addressed herein.